Photocatalytic applications of metal oxide-based nanocomposites for sustainable environmental remediation - Sahu, Sangram Keshari; Palai, Amrita; Sahu, Dojalisa (Sustainable Chemistry for the Environment, 2024)
Change in human lifestyle and excessive use of commercial products have caused an ecological deterioration. A major contribution towards this comes from the mixing of toxins and persistent organic pollutants into water bodies, which poses a serious risk to the ecosystem. In the above context, materials scientists are involved in the search for sustainable solutions to address the above environmental challenges by the development of advanced materials. In this study, we prepared nanocomposite materials such as; ZnO-SnO2 and ZnO-MoS2 by wet-chemical approach to degrade dye pollutants like Rhodamine B (RhB) and Congo red (CR) towards achieving environmental remediation. Powder X-ray diffraction (PXRD) measurement was done for structural characterization of the samples and the formation of the nanocomposite phase was validated by the above study. The goal of the field emission scanning electron microscopy (FESEM) study was to examine the morphology of the composites which was accompanied by the energy dispersive analysis of x-rays (EDAX) and electron mapping experiments which verified the presence of Zn, Sn, O, Mo, S elements in the respective samples. Fourier transformed infrared spectroscopy (FTIR) meas urement was conducted to investigate the vibrational properties of the samples. Photocatalytic measurement showed improved degradation efficiency of the composites as compared to the pristine samples. The degradation efficiency was found to increase with irradiation time and attained saturation after 180 min. ZnO-SnO2 nanocomposite show 91.23 % and 88.11 % of degradation for RhB and CR dyes respectively whereas 89.29 % and 83.25 % degradation have been obtained for ZnO-MoS2 for the same dyes. Several aspects of the experiment were varied, including the amount of catalyst employed, the initial dye concentration, and the pH levels, in order to assess the efficacy of the photocatalysts. Both the photocatalysts degraded CR dye most effectively at acidic pH, although RhB dye gets degraded more at neutral and alkaline pH. ZnO-SnO2 was found to be an effective photocatalyst for degrading RhB dye at neutral pH and CR dye at acidic pH. After multiple iterations of experimentation, the photocatalytic mechanism has been extensively described, and the stability and reusability of the photocatalysts have been ensured for effective environmental cleanup. [Display omitted] •Preparation of metal oxide based nanocomposites by wet chemical method.•ZnO-SnO2 and ZnO-MoS2 nanocomposites show enhanced photodegradation efficiency.•Promotion of charge separation and production of reactive oxygen species.•Nanocomposite photocatalysts are highly stable and reusable